2019
DOI: 10.1016/j.worlddev.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Do youth employment programs improve labor market outcomes? A quantitative review

Abstract: Bringing young people into productive work is a key labor market challenge in both developing and developed economies, and a multitude of labor market interventions have been implemented to assist vulnerable youths. To assess whether these interventions have succeeded in improving young people's labor market outcomes, this study systematically and quantitatively reviews 113 impact evaluations of youth employment programs worldwide. Of a total of 3,105 effect estimates we extract from these studies, one-third a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 172 publications
(148 citation statements)
references
References 23 publications
12
130
0
6
Order By: Relevance
“…As shown Kluve et al (2016), incentives and profiling measures were correlated with better employment and earnings outcomes. The Adolescent Girls Employment Initiative (AGEI) of the Employment Fund in Nepal provided technical and life skills training with a comprehensive incentive scheme.…”
Section: ) Recent Evidence Points To the Relevance Of Incentives Andmentioning
confidence: 78%
See 2 more Smart Citations
“…As shown Kluve et al (2016), incentives and profiling measures were correlated with better employment and earnings outcomes. The Adolescent Girls Employment Initiative (AGEI) of the Employment Fund in Nepal provided technical and life skills training with a comprehensive incentive scheme.…”
Section: ) Recent Evidence Points To the Relevance Of Incentives Andmentioning
confidence: 78%
“…However, as it was possible that the analysis could have been confounded with other intervention‐ or study‐level characteristics that were correlated with programme scale (e.g., country income level), this difference was explored in more detail as part of the multivariate meta‐analysis depicted in Kluve et al (2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a recent systematic review of 113 impact evaluations that considered employability and/or earnings of target populations found that only 30 per cent of employment training programmes are successful, typically with small effect (Kluve et al ., ). A significant proportion of the ‘non‐successful’ programmes were underpowered and inconclusive.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Like Kluve et al . (), the World Bank () calls for better data on outcomes, to hold ‘providers accountable for results’, among other uses.…”
Section: Literature Reviewmentioning
confidence: 99%